Relationship of Knowledge Stress, Consumption Patterns and Sport Patterns of PMS (Premenstrual Syndrome) in Adolescent Girls of SMP IT Yayasan Hj. Fauziah Binjai in 2019 - Nurrahmaton Nurrahmaton (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2021)
According to WHO, in 2016 PMS (premenstrual syndrome) has a higher prevalence in Asian countries compared to Western countries. PMS is discomfort or physical and mental symptoms that arise when a woman will experience a menstrual cycle. This study aims to determine the factors related to the occurrence of PMS in adolescent girls of SMP IT Yayasan Hj. Fauziah Binjai in 2019. This research used analytical survey with cross sectional approach. The study was conducted from February to August 2019. The populations were all adolescent girls of SMP IT Yayasan Hj. Fauziah Binjai amount 154 people and the sampling using stratified random sampling formula as many as 60 people. Data obtained by using observation sheets and analyzed by univariate and bivariate analysis. Bivariate analysis using Chi Square statistical tests at α = 5%. Results showed the statistical test results using chi square test, for the knowledge variable obtained p-value = .116> α .05, then Ho was accepted and for stress variables, consumption patterns, sports patterns obtained calculation results p-value = 0,000, then Ho was rejected and Ha was accepted. The conclusion shows that there is no relationship of knowledge with Premenstrual Syndrome and there is a relationship between stress, consumption patterns, sports patterns with premenstrual syndrome in SMP IT Yayasan Hj. Fauziah Binjai in 2019.